Dataset generated and used for “A unified framework for geometry-independent operator learning in cardiac electrophysiology simulations” - Bei Zhou (22682549) (2025)
The data referred to in the manuscript as ‘Dataset A’ are publicly available here. The repository includes two folders: Meshes, containing the left-atrium mesh files for 100 patients, and Dataset, containing all electrophysiology simulation data.